Religiöse Gewalt in historischer Dimension - Weltecke, Dorothea (De Gruyter Oldenbourg, 2025)
For the first time, historians try to systematically answer this question using their own methods. They scrutinize definitions and examine the relationships between acts of violence and their legitimation. By carrying out empirical analyses of various periods, cultures and regions, they the reveal epoch-specific characteristics and historical transformations of a lingering contemporary problem
Keywords: Konferenzschrift -- Historisches Kolleg (München) -- 2020 -- München; Geschichte; Gewalttätigkeit; Religiöser Konflikt; Religion; Gewalt